Propuesta de desarrollo turístico en la comunidad de Yacubiana, parroquia Salinas, cantón Guaranda, año 2018. - Velarde Ubilla, Hibeth Sheralee. (2019)
The present investigative study was carried out with the purpose of elaborating a tourism development proposal in the community of Yacubiana, belonging to the parish of Salinas of the Guaranda canton, so that in order to fulfill the objectives set out in the research, it was used of a descriptive methodology, which allowed to perform a search and be able to specify the characteristics and attributes of the subjects and objects of analysis or study, in addition to field research techniques and bibliographic research. In the community of Yacubiana the diagnosis was made to determine the current situation in the social, economic, sociocultural, environmental and tourism for which the inductive and deductive methods were used through the application of surveys and interviews conducted with the inhabitants of the community. The inventory of tourist attractions was made with the use of the deductive method, taking into account the methodology for the elaboration of inventory of tourist attractions of the Ministry of Tourism update 2017. Where ten tourist attractions were identified, of which six are cultural manifestations and four are natural attractions, thus determining the tourist potential of the community. In addition, a tourist guide, a tourism script and a community tour package were developed using the deductive method to determine the activities that can be developed in each of the attractions, and through these tools generate integration and community development.